The Pursuit of Permanence : a Study of the English Child Care System. - Sinclair, Ian, 1938- (Quality Matters in ChildrenÆs Services., 2007)
Children in public care complain that they have too many placements. Professionals agree but little is known about the reasons for this instability or how it affects different groups of children. The Pursuit of Permanence explores this core issue for children's services. Based on the largest study of the English care system in recent years, the book examines the children (what they need and what they want), their movements into, out of and within the care system, the nature and quality of their placements and the outcomes (whether the children are settled or happy). It analyses the reasons for.